Completely decentralised active balancing battery management system - Frost, D; Howey, D (Institute of Electrical and Electronics Engineers, 2017)
The performance of a string of series-connected batteries is typically restricted by the worst cell in the string and a single failure point will render the entire string unusable. To address these issues, we present a decentralised battery management system with no communication requirement based on a modular multilevel converter topology with a distributed inductor and distributed controller running on a local microprocessor. This configuration is referred to as a “smart cell”. By sensing the voltage across the local distributed inductor, each smart cell is able to (1) determine its optimal switching pattern in order to minimize the output voltage ripple, and (2) adjust its duty cycle to synchronize its state of charge with the average state of charge of the series string of cells. The decentralized controller is derived using the theory of Kuramoto oscillators, and the stability of a system of smart cells is investigated. We show experimentally that a system of three smart cells with their decentralized controllers can accurately synchronize the state of charge while minimizing their output voltage ripple.